2021
DOI: 10.1111/lam.13417
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity and synergy of antibiotics with sanguisorbigenin isolated from Sanguisorba officinalis L. against methicillin‐resistant Staphylococcus aureus

Abstract: Significance and Impact of the Study: Methicillin-resistant Staphylococcus aureus is the pathogen represents a considerable burden on the healthcare system worldwide, and resistance to nearly all β-lactam antibiotics. For the first time, we evaluated the antibacterial activity and the synergy of the sanguisorbigenin (SGB) combined with β-lactam antibiotics against methicillin-resistant S. aureus. The result indicated that SGB has a potent antibacterial effect and could effectively reverse the sense of β-lactam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
3
0
1
Order By: Relevance
“…MIC values of medicinal plants were determined using the broth microdilution method as follows: CS (62.5 µg/mL), GU (250 µg/mL), SO (250 µg/mL), and UG (250 µg/mL) [25]. Information on the plants and their pharmacological uses is presented in Table 1 [26][27][28][29][30].…”
Section: Resultsmentioning
confidence: 99%
“…MIC values of medicinal plants were determined using the broth microdilution method as follows: CS (62.5 µg/mL), GU (250 µg/mL), SO (250 µg/mL), and UG (250 µg/mL) [25]. Information on the plants and their pharmacological uses is presented in Table 1 [26][27][28][29][30].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we speculated that BDMC might also inhibit α-toxin production by the agr system, which would inhibit biofilm formation. Since biofilms are usually highly resistant to conventional antibiotics, the development of natural antibacterial substances with anti-biofilm activity may be of great significance [33].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the combination of natural active substances and conventional antibiotics can exhibit good synergistic effects against MRSA ( Wang et al, 2021 ). Our experimental results showed that AP can inhibit the transcription of S. aureus hla and its related genes at the genetic level to suppress the expression of related proteins, thereby reducing the hemolytic activity of S. aureus on host cells.…”
Section: Discussionmentioning
confidence: 99%